Coumel tachycardia in children - Enrique Velázquez-Rodríguez; Norberto García-Hernández; Arturo Martínez-Sánchez; Carlos Alva-Espinoza; Lucelli Yáñez-Gutiérrez; Santiago Jiménez-Arteaga (Permanyer, 2023)
Background: Coumel tachycardia is an infrequent form of supraventricular tachycardia (SVT) that usually occurs in infants and children. It is a tachycardia mediated by an accessory pathway with retrograde slow conduction that explains the classic ECG pattern with long RP' interval and negative P waves in leads II, III, and aVF. In this study, we describe the clinical course and management of Coumel tachycardia in children. Case report: We conducted a retrospective review of five consecutive pediatric patients, mean age 11 ± 3 years (range 6 to 14). The first episode of SVT was at a mean age of 10.4 ± 4.8 years (range 2 to 14) with a mean evolution of 7.4 ± 9.4 months (range 1 to 24). Pharmacological therapy was unsuccessful despite the combination of antiarrhythmic drugs. The tachycardia was incessant with a density > 85% by 24-hour Holter monitoring; one patient developed tachycardia-induced cardiomyopathy. All children underwent successful radiofrequency catheter ablation, mean 5 ± 3 applications (range 1 to 8) with a single session and with no complications. After a mean follow-up of 24 ± 16 months, all patients were asymptomatic and recurrence-free without antiarrhythmic treatment. Conclusions: Coumel tachycardia is clinically persistent and usually refractory to antiarrhythmic treatment with substantial risk of tachycardia-mediated cardiomyopathy. Catheter ablation is effective and safe in children; thus, it should be indicated promptly and based on individual selection.